Comparison of the anesthetic effect of alkalized lidocaine versus non-alkalized lidocaine administered at a slow rate in mandibular primary molars - Karen Torres-Rojas; Victor Chumpitaz-Cerrate; Lesly Chávez-Rimache; Daniella Núñez-Díaz; Vanessa Pérez-Jimenez (Tabriz University of Medical Sciences, 2023)
Background. There are several invasive dental procedures that require local anesthetics. However, its infiltration is usually associated with anxiety and fear, increasing the perception of pain in pediatric patients. For this reason, it is important to evaluate different strategies for its application. We compared the anesthetic effect of the administration of 2% lidocaine with epinephrine 1:80000 non-alkalized at slow speed and alkalized at fast speed to block the inferior alveolar nerve in deciduous molars. Methods. A crossover clinical trial was carried out whose sample consisted of 38 patients between 6-10 years who required bilateral pulp treatment in their first mandibular primary molars. At the first appointment, they received 2% lidocaine with 1:80000 alkalinized epinephrine administered at a fast rate, and at the second appointment, 2% lidocaine with 1:80000 non-alkalized epinephrine administered at a low speed. We evaluated the onset of action, duration of the anesthetic effect, and intensity of pain during its infiltration. Results. We found that non-alkalized lidocaine at slow speed had a shorter onset time of action (57.21±22.21 seconds) and longer duration of effect (170.82±43.75 minutes) compared to administration of alkalinized lidocaine at fast speed (74.03±22.09 seconds, 148.24±36.24 minutes, respectively). There was no difference in the level of pain intensity. Conclusion. In this study, the slow administration of the non-alkalized local anesthetic showed a shorter onset time of action and a longer duration of the anesthetic effect in comparison with the alkalized local anesthetic administered at a rapid rate in the blockade of the inferior alveolar nerve in deciduous molars.